Analysis of Indicators and Variables: An Overview of Marketing Capability for Engagement Based on Islamic Education - Ade Parlaungan Nasution; Sumitro Sarkum; Denny Ammari Ramadhan; Ajeng Handayani Purwaningrum (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The purpose of this study is to review and analyze the indicators of market knowledge variables, multi-actor engagement marketing systems (customers, employees, supply chain, dynamic marketing), as well as business performance variables. Current research needs to validate new digital business research indicators for capabilities from a marketing perspective through supply chain integration into multi-actor engagement in the digital era based on Islamic education. The method used is literature analysis and descriptive statistical analysis with the index method to provide an empirical picture. Findings about respondents' perceptions of indicators for future research directions could test some of the ability to identify real markets; ability to identify competitors; ability to identify new business trends; and the ability to identify the accuracy of forecasting profitability and revenue. Management capability and agility in the market require a strategy of carrying out unstable activities as a competitive advantage in maintaining business performance. It also involves the use of Islamic principles and values embodied in the Islamic religion in marketing efforts.